Bioadhesive 3D-Printed Skin Drug Delivery Polymeric Films: From the Drug Loading in Mesoporous Silica to the Manufacturing Process - Rafaela Santos de Oliveira; Nadine Lysyk Funk; Juliana dos Santos; Thayse Viana de Oliveira; Edilene Gadelha de Oliveira; Cesar Liberato Petzhold; Tania Maria Haas Costa; Edilson Valmir Benvenutti; Monique Deon; Ruy Carlos Ruver Beck (MDPI AG, 2022)
The alliance between 3D printing and nanomaterials brings versatile properties to pharmaceuticals, but few studies have explored this approach in the development of skin delivery formulations. In this study, clobetasol propionate (CP) was loaded (about 25% w/w) in mesoporous silica nanomaterial (MSN) to formulate novel bioadhesive and hydrophilic skin delivery films composed of pectin (5% w/v) and carboxymethylcellulose (5% w/v) by 3D printing. As a hydrophobic model drug, CP was encapsulated in MSN at a 3:1 (w/w) ratio, resulting in a decrease of CP crystallinity and an increase of its dissolution efficiency after 72 h (65.70 ± 6.52%) as compared to CP dispersion (40.79 ± 4.75%), explained by its partial change to an amorphous form. The CP-loaded MSN was incorporated in an innovative hydrophilic 3D-printable ink composed of carboxymethylcellulose and pectin (1:1, w/w), which showed high tensile strength (3.613 ± 0.38 N, a homogenous drug dose (0.48 ± 0.032 mg/g per film) and complete CP release after 10 h. Moreover, the presence of pectin in the ink increased the skin adhesion of the films (work of adhesion of 782 ± 105 mN·mm). Therefore, the alliance between MSN and the novel printable ink composed of carboxymethylcellulose and pectin represents a new platform for the production of 3D-printed bioadhesive films, opening a new era in the development of skin delivery systems.